2004
DOI: 10.22358/jafs/74068/2004
|View full text |Cite
|
Sign up to set email alerts
|

<i>Bos indicus</i> cattle can maintain feed intake and fat reserves in response to heat stress better than <i>Bos taurus</i> cattle

Abstract: Bos indicus cattle are better adapted to tropical conditions than Bos taurus breeds and in part this may be related to differences in lipid and carbohydrate metabolism during heat stress. Bos indicus and Bos taurus cattle were subjected to heat stress and blood samples obtained to measure metabolism. Heat stress decreased feed intake and increased plasma non-esterifi ed fatty acids (NEFA) in Bos taurus but not in Bos indicus cattle. Also, Bos indicus appear to be more insulin resistant than Bos taurus cattle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The significantly longer feeding duration during the daytime in Ongole-cross cattle indicates better heat resistance than in Simmental-cross cattle. A decrease in feed intake does not occur in Bos indicus cattle raised in hot temperatures (26 -32 °C), but it occurs in Bos taurus cattle from day 11 onwards [16]. Conversely, Simmental-cross cattle lie more during the daytime than Ongole-cross cattle.…”
Section: Behaviour Analysismentioning
confidence: 92%
See 1 more Smart Citation
“…The significantly longer feeding duration during the daytime in Ongole-cross cattle indicates better heat resistance than in Simmental-cross cattle. A decrease in feed intake does not occur in Bos indicus cattle raised in hot temperatures (26 -32 °C), but it occurs in Bos taurus cattle from day 11 onwards [16]. Conversely, Simmental-cross cattle lie more during the daytime than Ongole-cross cattle.…”
Section: Behaviour Analysismentioning
confidence: 92%
“…Bos taurus has fewer sweat glands and produces less sweat than Bos indicus. This is one of the supporting factors for Bos indicus having higher heat resistance than Bos taurus, in addition to their lower metabolic rate [16]. Limitations in Bos taurus force them to increase and accelerate ventilation rates, thereby enhancing evaporation through respiration.…”
Section: Physiological Responsesmentioning
confidence: 99%
“…What is certainly known, is that B. indicus cattle are more resistant to high temperatures than B. taurus . Beatty et al [ 73 ] suggested that B. taurus breeds have less resistance to heat stress, a subsequent reduced feed intake and raised plasma non-esterified fatty acids compared to B. indicus . The ability to tolerate heat in B. indicus is manifested in their reproductive ability to raise follicles capable of fertilization [ 74 ].…”
Section: Reproductive Performancementioning
confidence: 99%
“…Meanwhile, in some months of the year, high temperatures, high humidity values, plus solar radiation during the day, promote environmental conditions in which animals are unable to maintain body temperature [6]. These conditions being particularly harsh for Bos taurus cattle [7].…”
Section: Introductionmentioning
confidence: 99%